Análisis del comportamiento de la regla fiscal y el papel de los fondos de estabilización frente a la caída de los precios internacionales del petróleo (2018)
With the current economic situation, low international growth, volatility in the markets of the world's major economies, it is important to assume a fiscal policy stance that possesses the necessary tools to protect the Colombian economy in the best possible way. Therefore, maintaining the sustainability of public finances in the long term has been one of the objectives of the Central National Government of Colombia (GNC), for which the latter had as its best option the implementation of a Fiscal Rule, with which limits are established to the aggregate fiscal indicators. This paper describes the macroeconomic context that led the CNG to implement Law 1473 of 2011, Fiscal Rule; the impact of the Colombian economy in the face of the fall in international oil prices and the role played by the stabilizing funds as anti-cyclical fiscal policy tools for the period 2011-2016